2019
DOI: 10.18203/2320-1770.ijrcog20196022
|View full text |Cite
|
Sign up to set email alerts
|

Study of ectopic pregnancy in a tertiary care centre

Abstract: Background: Ectopic pregnancy is an obstetric emergency with high morbidity and mortality. Incidence of ectopic pregnancies has been increasing in last two to three decades with reduction in mortality. The presenting symptoms include irregular vaginal bleeding. The present study was undertaken to study the clinical features of ectopic pregnancies in a tertiary care hospital.Methods: The present study on ectopic pregnancies was carried out in department of obstetrics and gynaecology, jhalawar medical college, J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 4 publications
(4 reference statements)
3
8
0
Order By: Relevance
“…13,[15][16][17][19][20][21]23,28,29 The right side was more frequent than the left which was consistent with different other studies. 16,18,21,23,26,29 Our hospital being a tertiary level referral centre, 60.2% of the women had ruptured ectopic pregnancies which is comparable to most of the studies ranging from 56% to 91.5%. 4,13,17,19,21,26 Since most of the patients had ruptured ectopic pregnancy, they required emergency laparotomy and salpingectomy (81.8%) as life saving measures.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…13,[15][16][17][19][20][21]23,28,29 The right side was more frequent than the left which was consistent with different other studies. 16,18,21,23,26,29 Our hospital being a tertiary level referral centre, 60.2% of the women had ruptured ectopic pregnancies which is comparable to most of the studies ranging from 56% to 91.5%. 4,13,17,19,21,26 Since most of the patients had ruptured ectopic pregnancy, they required emergency laparotomy and salpingectomy (81.8%) as life saving measures.…”
Section: Discussionsupporting
confidence: 68%
“…17 The majority of ectopic pregnancy cases occurred in 30 to 34 years age group (28.4%) which was similar to a study by Kaveri et al, 16 (31 to 35 years). However, other studies [17][18][19] found more of these cases in 20 to 30 years age group. In this study, more of ectopic pregnancy was seen in multiparous (65%) which is similar to various other studies.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…1 EP is an important cause of maternal mortality and morbidity in the 1 st trimester. 2 Incidence of EP varies from 1-2 per 100 pregnancies globally. 3 Delays in diagnosis and treatment can make EP an acute emergency.…”
Section: Introductionmentioning
confidence: 99%